Ne-liquefaction system development for the 940 nm infrared optical characteristics measurement. (January 2022) - Zhang, Hengcheng; Xie, Wei; Meng, Shuai; Wu, Shanshan; Wang, Xiaojun; Chen, Zhongzheng; Huang, Chuanjun; Huang, Rongjin; Li, Laifeng
Highlights: A Ne-liquefaction system cooled by a G-M cryocooler was developed and the refractive index and transmission of 940 nm infrared in liquid neon were also measured. The neon gas was liquefied while the condenser chamber temperature was cooled down to 26.7 K and the production rate of liquid neon was 0.52 L/h. The refractive index and transmittance of 940 nm infrared in liquid neon are 1.103 and 99.85%, respectively. Abstract: A Ne-liquefaction system cooled by a G-M cryocooler was developed. The heat load and liquefied rate of the system were analyzed theoretically. The neon gas was liquefied over 340 min while the condenser chamber was cooled down to 26.7 K. The gas pressures of the heat exchanger inlet and condenser are directly proportional to its absolute temperature, which decreased with the reduction of cryostat system temperature. The pressure of the heat exchanger inlet decreased from 105 kPa to 100.4 kPa with the pressure of the condenser decreased from 101 kPa to 100.1 kPa. Neon gas with a purity of 99.999% was used in liquefaction and the mass flow is set to 0.173 g/s. The production rate of liquid neon is determined to be 0.52 L/h. The liquid neon was collected in a glass vacuum dewar with a transparent window, which allows to observe the liquid level and conduct the optical tests. The refractive index and transmittance of the 940 nm infrared in liquid neon are 1.103 and 99.85%, respectively. The parameters will provide a valuable database on infrared equipment with liquid neon as a cryogen.